Physicochemical Studies on Nafion® Modified ZnO Interlayers for Enhanced Electron Transport in the Inverted Polymer Solar Cells. Issue 35 (17th September 2018) - Remya, R.; Gayathri, P. T. G.; Unni, K. N. N.; Deb, Biswapriya
Abstract: Electron selective intermediate layers are crucial for both efficiency and stability of the inverted polymer solar cells (I‐PSCs). In this paper, an established low‐temperature (<130 °C) recipe to fabricate nano zinc oxide (ZnO) layers (L‐ZnO) exhibited typical values of power conversion efficiency (PCE∼3.3%) with the standard P3HT:PC61 BM blend. However, PCEs showed further improvement up to ∼24% (∼ 4.08%) when these layers were annealed at 300 °C (H‐ZnO). This annealing step can be bypassed by adopting a slightly different chemistry using Nafion as a modifier (NM‐ZnO). I‐PSCs fabricated with NM‐ZnO showed nearly 40% increase in the PCE (∼4.62%) with PEDOT:PSS hole transport layers (HTL) that matches the so far highest recorded value for such a system. For the low‐bandgap polymer blend PBDTT‐FTTE:PC71 BM, a peak efficiency of ∼6.77% was obtained compared to ∼5.34% with L‐ZnO (∼28% increase). Our experiments revealed that these enhancements were due to a combination of benefits obtained from Nafion modification such as favourable positioning of work function (WF), high band gap (Eg) and better transport characteristics through the layer interfaces. Abstract : In this paper we investigated the electron transporting performance of ZnO interlayers with or without Nafion modification through investigating the fabricated IPSCs. Devices with NM‐ZnO showed ∼40% increment in the PCE (∼4.62%) compared to the L‐ZnO devices (∼3.3%) due to a combination of benefits obtained from Nafion modification such as the favourable tuning of work function (WF), high band gap (Eg) and better transport characteristics.